The Importance of Taking Psychology: A Comparison of Three Levels of Exposure. (October 2019) - Landrum, R. Eric; Gurung, Regan A. R.; Amsel, Eric
We compared the performance of senior psychology majors, introductory psychology students, and similarly aged individuals with no college psychology on seven different outcome measures including multiple-choice knowledge tests, attitudes, and open-ended scenarios requiring qualitative responses. On all measures, both senior psychology majors and introductory psychology students significantly outperformed individuals with no college psychology. However, the absolute magnitude of introductory psychology student performance would be depicted as a failing grade at most institutions (i.e., below 60% correct). We discuss this pattern of results in the context of judging the effectiveness of the major, the role of the introductory psychology course, and judging the effectiveness of the assessment/outcome measures utilized.